A CASE STUDY OF QUICK-O-BOOK- AN ONLINE APPOINTMENT BOOKING SYSTEM FOR PATIENTS IN NORTH-EAST INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The rising numbers of missed appointments,  needless and unwarranted waste of patient’s  appointment time have caused an impending  problem for the healthcare institutions as  well as the patients. Hence it is desirable to  intercede the healthcare system so as to provide  smooth, uninterrupted, and sustained care  for the patients. The traditional appointment  booking requires hard and tedious work to get a  doctor’s appointment. This paper is a case study  of Quick-o-Book an online system of booking  doctors’ appointments in North-East India. It  also discusses the products and services offered  by Quick-o-Book. The system was developed  by Biswajit Paul, an entrepreneur from Silchar.  Quick-o-Book provides the platform to facilitate  the booking and management of patients’  appointment bookings. It also provides the  healthcare workers an easy access and approaches  towards managing patients’ appointments and  generating relevant reports.  This case is a good example of how  entrepreneurs create new ventures in an attempt  to find solutions to the existing social problems.  It gives the readers an idea of the entrepreneurial  competencies and skills needed to overcome  existing problems. It tells the readers how  problems are resolved by investigating and  observing the current phenomenon. In the  area of medical appointment booking systems  at health centres, the case delves into the  various decisive factors to be considered while  developing an appointment booking system
Keywords: Entrepreneurship; Innovation; Waiting time; E-health; ICT; System architecture; etc